2015
DOI: 10.2527/jas.2015-9291
|View full text |Cite
|
Sign up to set email alerts
|

Zilpaterol hydrochloride improves feed efficiency and changes body composition in nonimplanted Nellore heifers1

Abstract: This research aimed to evaluate the effects of zilpaterol hydrochloride (ZH; MSD Animal Health, São Paulo, SP, Brazil) on the performance, carcass traits, serum metabolites, body composition, and gain composition of nonimplanted Nellore heifers. Nellore heifers ( = 72; average BW = 267 ± 16 kg; average 18 mo of age) were maintained in a feedlot system for 118 d. Heifers were separated into 2 groups: Control and ZH. The ZH group received ZH (8.3 mg/kg diet DM) for 30 d with 3 d of withdrawal before slaughter. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…Furthermore, the values were within the standards observed in studies using high-grain diets for finishing beef cattle (Bohrer et al, 2014;Cônsolo et al, 2014Cônsolo et al, , 2015Genther-Schroeder et al, 2016;Contadini et al, 2017). It is worth noting that the results for rump fat were higher than those for fat thickness, since the deposition of adipose tissue begins from the end towards the middle of the carcass.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, the values were within the standards observed in studies using high-grain diets for finishing beef cattle (Bohrer et al, 2014;Cônsolo et al, 2014Cônsolo et al, , 2015Genther-Schroeder et al, 2016;Contadini et al, 2017). It is worth noting that the results for rump fat were higher than those for fat thickness, since the deposition of adipose tissue begins from the end towards the middle of the carcass.…”
Section: Discussionsupporting
confidence: 73%
“…In near-term IUGR fetuses and in 3-week-old IUGR lambs, we have shown that expression of ADRβ2 mRNA is downregulated in adipose tissue and skeletal muscle Yates et al 2012a). This ADRβ2 deficiency could explain restricted growth and muscle accretion in IUGR offspring because stimulation with ADRβ2 agonists repartitions nutrients in growing animals to support anabolic protein accretion and energy-producing oxidative pathways (Byrem et al 1998;Consolo et al 2015;Cadaret et al 2017). Furthermore, deficiencies in glucose oxidation in IUGR fetal sheep and in adult humans born SGA from IUGR coincide with impaired proximal insulin signalling that may reflect the loss of counter-regulatory effects of adrenergic signalling (Hadcock et al 1992;Morisco et al 2005;Ozanne et al 2005; Thorn et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the meta-analysis conducted by Lean et al (2014), ZH supplementation increased HCW, LM area, and dressing percentage, whereas it decreased 12th-rib fat thickness. Plasma components related to nitrogen metabolism (plasma urea nitrogen [PUN]) have either decreased (Parr et al, 2014) or remained unchanged (Cônsolo et al, 2015) in response to ZH, whereas plasma constituents related to carbohydrate metabolism (i.e., glucose and lactate) were unaffected (Van Bibber-Krueger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%